2018
DOI: 10.1371/journal.ppat.1006960
|View full text |Cite
|
Sign up to set email alerts
|

Protection by and maintenance of CD4 effector memory and effector T cell subsets in persistent malaria infection

Abstract: Protection at the peak of Plasmodium chabaudi blood-stage malaria infection is provided by CD4 T cells. We have shown that an increase in Th1 cells also correlates with protection during the persistent phase of malaria; however, it is unclear how these T cells are maintained. Persistent malaria infection promotes protection and generates both effector T cells (Teff), and effector memory T cells (Tem). We have previously defined new CD4 Teff (IL-7Rα-) subsets from Early (TeffEarly, CD62LhiCD27+) to Late (TeffLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In our model, it was striking to observe that 70 days after the last SPZ challenge, in contrast to radiationattenuated SPZ immunization protocol, challenged MDR2 −/− mice only maintained a substantially elevated absolute numbers of CD4 Tcm cells, but not Tcm CD8 cells nor CD8 and CD4 Tem cells. This is also in contrast to P. chabaudiinfected mice that continue to generate Tem long time after parasite clearance (62). The discrepancies between these findings are very likely due to the particular genotype of mice used in our study and also to the particular inflammatory events taking place in Mdr2 −/− mice.…”
Section: Discussionmentioning
confidence: 55%
“…In our model, it was striking to observe that 70 days after the last SPZ challenge, in contrast to radiationattenuated SPZ immunization protocol, challenged MDR2 −/− mice only maintained a substantially elevated absolute numbers of CD4 Tcm cells, but not Tcm CD8 cells nor CD8 and CD4 Tem cells. This is also in contrast to P. chabaudiinfected mice that continue to generate Tem long time after parasite clearance (62). The discrepancies between these findings are very likely due to the particular genotype of mice used in our study and also to the particular inflammatory events taking place in Mdr2 −/− mice.…”
Section: Discussionmentioning
confidence: 55%
“…It is generally accepted in literature that TCM are long-lived with high differentiation potential and TEM are superior at effector functions, but at the expense of longevity, hence one of the factors contributing to temporal decay of malaria protective immunity. [224,386,387]. This proposed model of bi-linear differentiation was supported by numerous other studies in viral and bacterial infection models in both humans and mice, and highlights heterogeneity and plasticity of effector and memory T-cell differentiation and generation [388].…”
Section: Dcs In Plasmodium Infectionmentioning
confidence: 58%
“…However, Opata et al also reported that early TEFFE parallel differentiation into TCM  TEM was already programmed to occur during acute PccAS infection, in concordance with early TEFFE  late TEFFL differentiation by peak parasitemia and beyond [115,[386][387][388]. It is generally accepted in literature that TCM are long-lived with high differentiation potential and TEM are superior at effector functions, but at the expense of longevity, hence one of the factors contributing to temporal decay of malaria protective immunity.…”
Section: Dcs In Plasmodium Infectionmentioning
confidence: 90%
See 2 more Smart Citations